Answer: x=9,-1
Step-by-step explanation:
First, we are gonna start out with finding two numbers that multiply to equal -9 and add up to equal -8
Those numbers would be -9 & 1
-9+1=-8
-9x1=-9
Now we have
(x-9)(x+1)
x-9=0 x+1=0
+9 +9 -1 -1
x=9 x=-1
Answer:
-5(2) (-2) +2 + 4(-2) +7 = 21
-4(2) -2(-2) -10 = -14
21/14 = -1.5 or -1 1/2
Simplify 2.5 + 13.5 to 16
10 × 16
Simplify
160
Answer:
9
Step-by-step explanation:
Answer:
Step-by-step explanation:
We need to write the slope intercept form of the equation which passes through (4,-1) and parallel to the line y = -3/4x .
We know that the line parallel to a given line has the same slope . Therefore the slope of the line will be , ( on comparing to Slope Intercept Form ) .
On using point slope form ,
Substitute the respective values ,
Simplify ,
Multiply both sides by 4 ,
Put all terms on same side , i.e. on LHS ,
![\sf\longrightarrow \boxed{\pink{\sf 3x + 4y -8=0}}](https://tex.z-dn.net/?f=%5Csf%5Clongrightarrow%20%5Cboxed%7B%5Cpink%7B%5Csf%203x%20%2B%204y%20-8%3D0%7D%7D)
<u>Hence</u><u> the</u><u> </u><u>equation</u><u> of</u><u> </u><u>the</u><u> line</u><u> </u><u>is </u><u>3x</u><u> </u><u>+</u><u> </u><u>4</u><u>y</u><u> </u><u>-</u><u> </u><u>8</u><u> </u><u>=</u><u> </u><u>0</u><u>. </u>